Edukasi Literasi Keuangan bagi Santri di Pesantren Al-Marjan Mulabaru Lebak Banten - Yulia, Iis Anisa; Mutmainah, Isbandriyati; Susanto, Heri; Dewi Fitrianti; Rumna, Rumna; Pranamulia, Agus; Putra, Mulyana Gustira; Fitriani, Anna; Arifien, Yunus; Solihin, Lalu; Maad, Faizal; Marnilin, Feni; Rusman, Hedar; Wahidhani, Eha Hasni; Widjaja, Ichwan Rachmanu; Sukayat, Harmoko; Irawan, Rahmat; Mahfudi, Ahmad Zaid; anisa yulia, iis (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The Community Service Program (PkM) was implemented at Al-Marjan Mulabaru Islamic Boarding School, Lebak, Banten, to strengthen students’ financial literacy. Key challenges identified include low baseline financial knowledge, limited access to financing for pesantren-based enterprises, and insufficient infrastructure and technology (notably internet access and fintech tools) to support financial information and services. The program involved needs assessment, material development, face-to-face training, discussion, and evaluation using pre- and post-tests. Results show an increase in understanding from 43% (pre-test) to 92% (post-test), a gain of 49 percentage points. These findings indicate that the training content and delivery were effective in improving basic skills in budgeting and money management. Participants were highly engaged during the sessions, reflected in active discussions and question-and-answer activities.